Everyone's awake - Meloy, Colin (Chronicle Books, 2020)
"In this house, when everyone stays awake at night, things get very strange, what with Mom on the roof, and Grandma playing cards with the ghost of long-dead Grandpa Paul, and even the dog and cat are acting weird; as the family's doings become more and more bizarre, the narrator starts to wonder--what on earth will happen when morning finally comes." --